Optimal refrigerant charge and energy efficiency of an oil-free refrigeration system using R134a. (5th January 2020) - Li, Zhaohua; Jiang, Hanying; Chen, Xinwen; Liang, Kun
Highlights: Refrigerant charge and energy efficiency of an oil-free VCR system were investigated. Superheat increases with the refrigerant charge while subcooling shows a reverse trend. Cooling capacity and EER reach maximum value at the optimal refrigerant charge. Cooling capacity decreases and EER increases with condenser temperature. Higher compressor stroke has a higher optimal refrigerant charge. Abstract: Growing number of refrigerator and air conditioner units in recent years has rapidly increased the carbon emissions due to refrigerant leakage and energy demand. Operating a vapour compression refrigeration system with an optimal refrigerant charge can effectively increase energy efficiency and capacity, and minimise refrigerant leakage thus reduce global warming effect. This paper experimentally studies the optimal refrigerant charge and energy efficiency of a small oil-free refrigeration system for a wide range of operating conditions using R134a. The oil-free refrigeration system consists of two balanced linear compressors, an off-the-shelf condenser, an expansion valve and an evaporator with an electric heater. The condenser temperature, pressure ratio and compressor stroke were controlled allowing comparable test conditions for evaluating the system performance under various refrigerant charges. The experimental results show that at a condenser temperature of 40 °C, a pressure ratio of 3.5 and a compressor stroke of 13 mm, the oil-free refrigeration system can achieve an energy efficiency ratio (EER) of 9.0 with a refrigerant charge of 280 g. The maximum cooling capacity is 218.5 W at a compressor stroke of 13 mm and a pressure ratio of 3.5 with a refrigerant charge of 300 g. By increasing 20% condenser temperature or 25% compressor stroke, the optimal refrigerant charge of the oil-free refrigeration system is increased by 11%.